Development and initial validation of the Psychological Characteristics of Developing Excellence Questionnaire version 2 (PCDEQ2). Issue 4 (21st April 2019) - Hill, Andy; MacNamara, Áine; Collins, Dave
Abstract: Given sport's ever-increasing value and competitiveness, the race to identify and develop the next generation of sporting talent has never been more intense. Accordingly, in an effort to increase the effectiveness and efficiency of talent development, and recognising the critical role that psychology plays in these processes, this paper seeks to develop a formative assessment tool that will allow practitioners to measure and monitor the development of the psychological skills, characteristics and behaviours – both adaptive and maladaptive – that underpin effective development. Following a process of item generation and justification, a 135-item questionnaire was completed by 512 developing male athletes from academy-based team sports. Exploratory factor analysis was conducted to identify any underpinning latent factor structures, resulting in an 88-item, 7-factor solution that accounted for 40% of the explained variance, with an overall reliability of α  = 0.879. A subsequent discriminant function analysis was conducted and the questionnaire was able to correctly classify 72.9% of participants based on their responses. Accordingly, the Psychological Characteristics of Developing Excellence Questionnaire version 2 (PCDEQ2) provides talent development environments with a valid and reliable measure form which to base effective psycho-behavioural interventions, ultimately improving the effectiveness of talent development processes.